Gestión de cobranza y la recuperación de cartera de servicios en los Gad municipales de la zona 5 del Guayas - Rivera Brito, Kristy Lisset (2022)
The present research work is based on the correct application of guidelines and procedures as an efficient tool that facilitates the collection management of the Municipal Gad of zone 5, such as Balzar, Colimes and Santa Lucia. In this research work, it had a mixed approach, descriptive in scope with a non-experimental design, through which three interviews were carried out consisting of fourteen questions addressed to those in charge of the collection areas of municipal services. The results show that these public institutions lack strategies when managing collection activities in the values of services provided to users. Research that showed evidence of the lack of not correctly applying the collection processes in addition to not having internal collection guidelines and therefore there is no recovery of overdue portfolio. Within the proposal, the design of a methodology that contains strategies and a portfolio recovery manual was presented, specifying the functions of each agency responsible for collecting money in terms of Gad services, this for the benefit of these institutions and to make effective the fulfillment of the service the locality.